Modelling the Ammoniation of Barium Chloride for Chemical Heat Transformations - Samuel Hinmers; Robert E. Critoph (Energies, 2019)
The coupling of reversible ammoniation reactions between two salts presents a method for the exploitation of low grade waste heat. This resorption configuration can be used for thermal transformation or heat pumping, to recover waste heat to primary producers, or for integration in heat networks. To understand the solid/gas reaction behaviour and to model its kinetics, Large Temperature Jump (LTJ) experiments were performed on a composite of barium chloride in an expanded natural graphite (ENG) matrix. A model has been built using a semi-empirical equation from the literature, which has been validated with the LTJ results. The results suggest the semi-empirical model provides a reasonable prediction for solid/gas reactions once the constants have been identified. Enhancing the model to handle sequential phase change reactions will enable a wide number of salts to be modelled, making the design of a resorption system practicable.